Faktor- Faktor Yang Mempengaruhi Kinerja Pegawai Di Kantor Dinas Lingkungan Hidup Daerah Tapanuli Selatan - Putri Bunga Meiliana; Ella Zefriani Lisna; Rizki Pratiwi Harahap (CERED Indonesia Institute, 2023)
The type of research used in this study is a type of quantitative research using multiple regression analysis. The data collection technique used a questionnaire with a total of 48 employees with a saturated sampling technique formula. Data processing was carried out using SPSS Version 23. The data analysis tools used were validity tests to see whether the data was valid or not, reliability tests, normality tests to see whether the data were normally distributed, multicollinearity tests, heteroscedasticity tests, multiple regression tests, coefficient of determination tests, partial test (t test) and simultaneous test (f test). The results of the study with partial tests show that there is an influence of motivation on employee performance as evidenced by the tcount > t table test of 2.756 (2.756 > 2.014) and there is an influence of the work environment on employee performance as evidenced by the tcount > t table test of 7.480 (7.480 > 2.014).